Pemberdayaan UMKM Bakso Kemasan “Ada Rasa” Melalui Analisis Religiusitas Strategi Marketing di Jekulo Kudus - Kusrini, Eni (Universitas Islam Negeri Sunan Kudus, 2019)
Empowerment of UMKM as a forum for implementing the micro-economy to encourage economic growth nationally. This empowerment must be able to increase economic activity to the fullest. The existence of UMKM that are dominant as national economic actors is also a vital subject in development, because it is possible to expand opportunities for entrepreneurship, empowering workers, and reducing unemployment in a country in general. To create empowerment of UMKM as a mandate, it is necessary to have religious accountability in the implementation of UMKM. Religiosity is the internalization diversity that exists in a person as a form of devotion to religion at the behest of Allah SWT. Therefore, marketing strategies are needed in the success of UMKM based on rules.